Differential effects of synthetic media on long-term growth, starch accumulation and transcription of ADP-glucosepyrophosphorylase subunit genes in Landoltia punctata - Chokchai Kittiwongwattana (My University, 2019)
Abstract Murashige & Skoog (MS) and Hoagland’s media were previously used for in vitro culture of Landoltia punctata . During subsequent ex vitro culture, the use of MS medium resulted in a higher growth rate, compared to Hoagland’s medium. Thus, a higher starch content of L. punctata in MS medium was previously hypothesized. Here, L. punctata strain 5632 was isolated and characterized using morphological characteristics and the atpF - atpH intergenic region. During early cultivation stage, fresh weight and relative growth rate in MS medium were lower than Hoagland’s medium. Conversely, starch content in MS medium was considerably higher than in Hoagland’s medium. Medium effects on expression of genes coding for starch-biosynthesis ADP-glucosepyrophosphorylase (AGPase) were determined. Genomic fragments of small ( LeAPS ) and large ( LeAPL1 ) AGPase subunits were characterized. Differential expression between each AGPase subunit genes was observed in both media. Additionally, in MS medium, the highest correlation coefficients between starch content and gene expression was found with LeAPS (0.81) and followed by LeAPL3 (0.67), LeAPL2 (0.65) and LeAPL1 (0.28). In Hoagland’s medium, the coefficients of LeAPL3 (0.83) and LeAPL2 (0.62) were higher than LeAPS (0.18) and LeAPL1 (−0.62). This suggested different levels of contributions of these genes in starch biosynthesis in both media.
Keywords: LEAPS; Hoagland solution; Plant biochemistry; Enzyme Production and Characterization